FEATURES OF DRYING ZEOLITE 13X IN A MICROWAVE FIELD - Hrechanovskyi, Andrii (SWorld-Ger Conference proceedings, 2025)
It has been proven that zeolites currently have a wide range of applications due to their large pore surface area; zeolites for thermochemical heat storage are of particular interest due to their ability to provide high energy density. It is known that fo